2009
DOI: 10.1007/s10620-009-1026-7
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Abdominal Pain in Children Is Associated with High Prevalence of Abnormal Microbial Fermentation

Abstract: Similar to adults with IBS, there is a significantly higher prevalence of SIBO in children with CAP. Randomized controlled studies are needed to determine if eradication of SIBO will lead to symptom improvement in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 38 publications
2
28
0
2
Order By: Relevance
“…Although another recent interesting and well-conducted review of the literature examined the criteria for a positive breath test in IBS [33], new large-scale age-and sex-matched studies [28][29][30] have recently been published. In addition, this meta-analysis examines the more practical presence or absence of a positive result in case-control studies rather than the specific criteria used for testing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although another recent interesting and well-conducted review of the literature examined the criteria for a positive breath test in IBS [33], new large-scale age-and sex-matched studies [28][29][30] have recently been published. In addition, this meta-analysis examines the more practical presence or absence of a positive result in case-control studies rather than the specific criteria used for testing.…”
Section: Discussionmentioning
confidence: 99%
“…After application of paper review, 11 papers then proceeded to full review as they met all of the eligibility requirements [16,[21][22][23][24][25][26][27][28][29][30]. Ten of the 11 papers were written in English [16,[21][22][23][24][25][26][27][28][29][30], and one was in Italian [17]. This Italian paper was translated into English to acquire the data.…”
Section: Paper Selection Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…Few publications on the role of SIBO in the pathophysiology of functional gastrointestinal disorders in pediatric population are available. One study demonstrated 91% prevalence of SIBO in IBS, and 35% prevalence in controls [11]; another study showed a lower prevalence [12]. In both studies, an association among some symptoms analyzed in these patients and SIBO was established.…”
Section: Introductionmentioning
confidence: 90%
“…Kolejne dwa badania dotyczyły nie tyle pacjentów z IBS, co dzieci z przewlekłym bólem brzucha. Collins i Lin objęli badaniami 75 dzieci i młodzieży w wieku 8-18 lat z przewlekłym bólem brzucha spełniających II Kryteria Rzymskie [40]. Stwierdzono nieprawidłowy HBT z laktulozą u 91% pacjentów oraz u 35% z grupy kontrolnej.…”
Section: Introductionunclassified